Influence of an education program of pregnant women on delivery. (25th September 2013) - Martínez-Galiano, Juan Miguel; Delgado-Rodríguez, Miguel
Abstract: Objectives : To assess whether an education program of pregnant women influences factors related to delivery and health behavior with newborns after delivery, such as the establishment of early skin-to-skin contact between the mother and newborn. Methods : A multicenter observational study was carried out with primiparous women in four hospitals in southern Spain in 2011. Data on sociodemographic and obstetric variables were collected from interviews and clinical charts. In the analysis, crude and logistic regression adjusted odds ratios (ORs) were estimated. Results : The study population comprised 520 women, 354 of whom attended the education program (68.1%). The program favored the establishment of early skin-to-skin contact between the mother and newborn (aOR 1.95, 95% CI 1.25–3.02, after adjusting for sociodemographic characteristics and the presence of pathology during pregnancy). Mothers who attended the program participated more actively during delivery (aOR 1.64, 95% CI 1.16–2.31). No association was observed between attending the program and the type of delivery (aOR 0.79, 95% CI 0.53–1.1) or with the frequency of cesarean section (aOR 0.81, 95% CI 0.49–1.34). The duration of delivery was also unrelated to maternal education. Conclusions : Maternal education did not influence the type of delivery, but it favored women's participation during delivery and early skin-to-skin contact between the mother and newborn.